Relationship between microstructure and mechanical property of nickel aluminium bronze alloy solidified at different cooling rate and heat treated - Nurhaulia Razali, 1985- author; Muhamad Azizi Mat Yajid, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2014